PENGARUH SUBTITUSI TEPUNG AMPAS KELAPA DALAM PEMBUATAN PERMEN JELLY TERHADAP MUTU ORGANOLEPTIK, KADAR SERAT DAN DAYA TERIMA SISWA SEKOLAH DASAR - Putri Millenia Nurtsaniyah Hakim; M. Berri Ridhoka; Ana Verena Puspa Rini (Bajang Institute, 2025)
Fiber is a complex carbohydrate essential for digestive health. Coconut pulp is rich in fiber (17.6 g crude fiber; 7.14 g soluble dietary fiber; 43.8 g insoluble fiber/100 g) and therefore has the potential to be used in food products such as jelly candies, which are popular with children. The aim of this study was to determine the effect of coconut pulp flour substitution on the organoleptic quality, fiber content, and acceptability of jelly candies among elementary school students. The type of research is an experiment with a Completely Randomized Design (1 control, 3 treatments: F0 = 0 g, F1 = 45 g, F2 = 60 g, F3 = 75 g coconut pulp flour). Organoleptic tests were conducted by 25 semi-trained panelists (sixth semester students of the Nutrition Study Program of STIKes Husada Gemilang) on ​​June 17, 2025, dietary fiber tests at the Agricultural Product Analysis Laboratory of the University of Riau (June 23–July 8, 2025), and acceptance tests on 36 students of SDN 010 Sungai Beringin (July 19, 2025). Data analysis used Kruskal Wallis, followed by a 5% Post Hoc test if significantly different. The results showed that the substitution of coconut pulp flour significantly affected color, aroma, and texture (p<0.05), but not on taste. The best formulation was F2 (60 g) with the highest score: just the right sweetness, chewy-soft texture, light aroma, natural color, and fiber content of 11.65 g/100 g (up 4.3 g from the control). Children's acceptance of the best formulation (F2) was considered good (91.67%). In conclusion, the addition of 60 g of coconut pulp flour resulted in a high-fiber jelly candy that was well-liked and has the potential to be a healthy snack made from local ingredients. Further research is recommended to explore flavor variations, coconut pulp flour addition levels, shelf life testing, complete nutritional analysis, and acceptance across various age groups